Assessing the factors affecting the development of rural entrepreneurship: A case study of villages in Torbat-e Heydarieh, Kadkan district - Abbasi, Mostafa (2021)
Entrepreneurship is one of the most important tools for planning and achieving the development of rural communities. Today, due to the problems in these communities, attention and emphasis on rural entrepreneurship is very important; because entrepreneurship can with creation an effective role in improving the economic and living conditions of villages by creating new employment and income opportunities. This article has been written with the aim of evaluating the factors affecting the development of rural entrepreneurship in a case study of villages in Torbat-e Heydarieh, Kadkan district. The research method was descriptive-analytical and the data collection method was library and field. One-sample t-test with principal component analysis was used to analyze the data. The statistical population of the study was the villagers of Kadkan district of Torbat-e Heydarieh, from which 240 people were selected as a sample and they were asked to complete a questionnaire. To assess the validity of the questionnaire, the content and face validity technique was used with the judgment of experts on research questions. The reliability of the research instrument was determined using Cronbach's alpha coefficient, which is above 0.75 for all dimensions and indicates the desirable capability of the questionnaire. The results showed that among the factors affecting entrepreneurship, the economic factor is the most influential factor in the study area. The results also showed that rural entrepreneurship is one of the suitable fields for creating employment in agricultural and non-agricultural sectors and one of the important factors in achieving sustainable development in rural areas.